The burden of congenital birth defects between 1990 and 2019 in China: an observational study - Zhao, Yajun; Zhang, Haonan; Peng, Minghui; Zhou, Yemei; Cheng, Xuelin; Yang, Shijia; Zhang, Zhaoyu; Liu, Ming; Li, Xiaopan; Jiang, Sunfang (Frontiers in Pediatrics, 2023)
Background: Congenital birth defects (CBDs) are a major public health issue. This study aims to assess trends in the burden of CBDs between 1990 and 2019 across China based on the Global Burden of Disease Study 2019 (GBD2019). Methods: Indicators of the burden of CBDs included incidence, mortality, and disability-adjusted life years (DALYs). Metrics included number, rate, and age-standardized rate with 95% uncertainty intervals (UIs). Data were stratified by region (China, global, high-, middle-, low-socio-demographic index [SDI]), age, sex, and type of CBD. Average annual percentage changes (AAPC) and trends were evaluated. Results: In China, between 1990 and 2019, the age-standardized incidence rate for CBDs showed an increasing trend, with an AAPC of 0.26% (0.11% to 0.41%), reaching 148.12 per 105 person-years (124.03 to 176.33) in 2019. Most CBDs were congenital heart anomalies, with an AAPC of 0.12% (-0.08% to 0.32%). The age-standardized mortality rate for CBDs showed a decreasing trend, with an AAPC of -4.57% (-4.97% to -4.17%), reaching 4.62 per 105 person-years (3.88 to 5.57) in 2019. Most mortality was associated with congenital heart anomalies, with an AAPC of -3.77% (-4.35% to -3.19%). The age-standardized DALYs rate for CBDs showed a decreasing trend, with an AAPC of -3.74% (-3.95% to -3.52%), reaching 480.95 per 105 person-years (407.69 to 570.04) in 2019. Conclusions: Morbidity associated with CBDs increased in China between 1990 and 2019, accelerated by the adoption of the two-child policy, and ranked high globally. These findings emphasize the need for prenatal screening and primary and secondary prevention strategies.